2021
DOI: 10.1021/acsami.1c12180
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidation and Energy-Level Alignment for Improving Efficiency and Stability of Hole Transport Layer-Free and Methylammonium-Free Tin–Lead Perovskite Solar Cells

Abstract: Tin−lead (Sn−Pb) perovskites have shown great potential in applications of single-junction perovskite solar cells (PSCs) and tandem devices due to outstanding photoelectrical properties and low band gaps. Currently, Sn−Pb PSCs typically have a p−i−n structure, but choices of hole transport layer (HTL) materials are very limited and there are different concerns in each of them. Eliminating the HTL is a direct and promising strategy to address the concerns, but is rarely studied. In this work, we demonstrate HTL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 46 publications
0
21
0
Order By: Relevance
“…[59,[108][109][110] Liu et al, demonstrated a synergistic integration approach by uniting a reducing agent formamidine sulfonic acid (FSA) and in situ surface passivation together in Sn-Pb perovskites (FA 0.85 Cs 0.15 Sn 0.5 Pb 0.5 I 3 ) to enhance the performance of HTL-free and MA-free tin-lead mix PSCs, which exhibited a champion PCE of 17.4% with a bandgap of 1.27 eV. [111] This integration method appears to be more effective at preventing Sn 2+ oxidation and passivating the defect, resulting in a significantly lower trap density (1.65 × 10 15 for pristine and 1.08 × 1015 cm -3 for modified device), improved V TFL value (Figure 6d), better energy level alignment and enhanced charge carrier lifetime. Jesus et al have published a chemical engineering strategy based on adding dipropylammonium iodide (DipI) and sodium borohydride (NaBH 4 ) to prevent the early degradation of Snbased PSCs.…”
Section: Other Antioxidant/reductive Agentsmentioning
confidence: 99%
See 2 more Smart Citations
“…[59,[108][109][110] Liu et al, demonstrated a synergistic integration approach by uniting a reducing agent formamidine sulfonic acid (FSA) and in situ surface passivation together in Sn-Pb perovskites (FA 0.85 Cs 0.15 Sn 0.5 Pb 0.5 I 3 ) to enhance the performance of HTL-free and MA-free tin-lead mix PSCs, which exhibited a champion PCE of 17.4% with a bandgap of 1.27 eV. [111] This integration method appears to be more effective at preventing Sn 2+ oxidation and passivating the defect, resulting in a significantly lower trap density (1.65 × 10 15 for pristine and 1.08 × 1015 cm -3 for modified device), improved V TFL value (Figure 6d), better energy level alignment and enhanced charge carrier lifetime. Jesus et al have published a chemical engineering strategy based on adding dipropylammonium iodide (DipI) and sodium borohydride (NaBH 4 ) to prevent the early degradation of Snbased PSCs.…”
Section: Other Antioxidant/reductive Agentsmentioning
confidence: 99%
“…Reproduced with permission. [111] Copyright 2021, American Chemical Society. e) J−V curves of FASnI 3 perovskite device without and with NaBH 4 , DipI and both together.…”
Section: Other Antioxidant/reductive Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, all-perovskite tandems with an efficiency over 24% have been reported . Compared to Pb 2+ , Sn 2+ exhibits different characteristics, including easy oxidation and crystallization of perovskite. These features hamper the development of Sn-based PSCs with efficiency still lower than their Pb counterparts. Furthermore, most high-efficiency (>20%) Sn-Pb PSCs contain volatile methylammonium ions (MA + ) in perovskite composition and employ PEDOT:PSS (poly­(3,4-ethylenedioxythiophene):polystyrene sulfonate) as hole-transporting materials (HTMs), , yet both of them are detrimental to the stability of the resulting devices.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, most high-efficiency (>20%) Sn-Pb PSCs contain volatile methylammonium ions (MA + ) in perovskite composition and employ PEDOT:PSS (poly­(3,4-ethylenedioxythiophene):polystyrene sulfonate) as hole-transporting materials (HTMs), , yet both of them are detrimental to the stability of the resulting devices. Especially, PEDOT:PSS exhibits strong acidity, hygroscopic nature, and shallow HOMO (highest occupied molecular orbital) value, , greatly limiting its scalable application in tandems.…”
Section: Introductionmentioning
confidence: 99%